2023
DOI: 10.1093/oxfclm/kgad001
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of descriptive and dynamic norms in promoting climate change advocacy

Abstract: Political advocacy is arguably the most powerful form of action that citizens concerned about climate change can take. One motivator for political advocacy is the perception that there is a social norm (i.e., inherently understood social rules and standards that serve to guide social behaviors) for doing so. Using nationally representative survey data (N = 1,303), we examined the association of three types of social norms—descriptive norms (i.e., perceptions about how many other people perform a behavior) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Political participation. The items for this measure were taken from existing scales [25][26][27][28][29][30][31][32][33] and adapted for the climate topic and the German context [10]. The final scale consisted of 11 items reflecting conventional participation (e.g., signing petitions), activism (e.g., participating in demonstrations), and peer group-related participation (e.g., discussions with friends).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Political participation. The items for this measure were taken from existing scales [25][26][27][28][29][30][31][32][33] and adapted for the climate topic and the German context [10]. The final scale consisted of 11 items reflecting conventional participation (e.g., signing petitions), activism (e.g., participating in demonstrations), and peer group-related participation (e.g., discussions with friends).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Over time, more Americans are moving toward the alarmed and concerned groups (Leiserowitz et al, 2023). Their survey data from December 2022 also showed that one in ten Americans reported feeling distressed about global warming, and the climate distressed are more likely to take actions such as signing a petition or volunteering at an organization on global warming (Ballew et al, 2023).…”
Section: Recent Public Opinions About Climate Changementioning
confidence: 99%
“…12 statements into 25 categories (35,36,(68)(69)(70)(71)(72)(73)(74). Then, one item was developed for each category, and those items were tested as indicators of general participation (i.e., not contextualized to climate change).…”
Section: Mg Et Al)mentioning
confidence: 99%